Pengaruh Edukasi Perawatan Tali Pusat Bayi Baru Lahir terhadap Pengetahuan Ibu Nifas di RSIA Murni Teguh Rosiva Medan - Mei Melda Napitupulu; Harsudianto Silaen (Quantum Wellness : Jurnal Ilmu Kesehatan, 2025)
The umbilical cord is the main entry point for systemic infection in newborns. Umbilical cord care aims to prevent infection and accelerate the breaking of the umbilical cord. Some postpartum mothers have insufficient knowledge about umbilical cord care so that education is needed. This study aims to determine the effect of education on newborn umbilical cord care on postpartum mothers' knowledge. This research method is a quantitative pre-experimental study using the One Group Pre Test-Post Test without control approach. The study was conducted at RSIA Murni Teguh Rosiva Medan. The population was 101 patients per month and 47 samples were obtained. Sampling was done randomly. Analysis was carried out univariately in a frequency distribution table and bivariately using the Paired Sample T-Test because the data was normally distributed. The results of the study showed that before being given education (pretest) the majority of postpartum mothers had poor knowledge (53.2%) with an average value of 5.09 ± 1.501, after being given education (posttest), the majority of postpartum mothers had good knowledge (70.2%) with an average value of 8.19 ± 1.096. Providing education on newborn umbilical cord care had a significant effect on increasing the knowledge of postpartum mothers at RSIA Murni Teguh Rosiva Medan, obtained p-value = 0.000 <0.05. There was a difference in the knowledge of postpartum mothers before and after being given education on newborn umbilical cord care (pretest-posttest). The conclusion of the study was that mothers' knowledge of umbilical cord care increased after being given education. It is recommended for further researchers to conduct further research using other research variables such as attitudes, motivations, perceptions, and others, to complement the existing research results.